В объятиях призрака: роман / Е. А. Арсеньева - Арсеньева Е. А. (Соблазны, 1997)
Экземпляры: (20170705) / Инвентарный номер: 30287 / Цена: 31.00 / Сис.шифр: Р2 / Авт.знак: А 85 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6